An iterative gene‐editing strategy broadens eIF4E1 genetic diversity in Solanum lycopersicum and generates resistance to multiple potyvirus isolates. Issue 5 (30th January 2023) - Kuroiwa, Kyoka; Danilo, Benoit; Perrot, Laura; Thenault, Christina; Veillet, Florian; Delacote, Fabien; Duchateau, Philippe; Nogué, Fabien; Mazier, Marianne; Gallois, Jean‐Luc
Summary: Resistance to potyviruses in plants has been largely provided by the selection of natural variant alleles of eukaryotic translation initiation factors ( eIF ) 4E in many crops. However, the sources of such variability for breeding can be limited for certain crop species, while new virus isolates continue to emerge. Different methods of mutagenesis have been applied to inactivate the eIF4E genes to generate virus resistance, but with limited success due to the physiological importance of translation factors and their redundancy. Here, we employed genome editing approaches at the base level to induce non‐synonymous mutations in the e IF4E1 gene and create genetic diversity in cherry tomato ( Solanum lycopersicum var. cerasiforme ). We sequentially edited the genomic sequences coding for two regions of eIF4E1 protein, located around the cap‐binding pocket and known to be important for susceptibility to potyviruses. We show that the editing of only one of the two regions, by gene knock‐in and base editing, respectively, is not sufficient to provide resistance. However, combining amino acid mutations in both regions resulted in resistance to multiple potyviruses without affecting the functionality in translation initiation. Meanwhile, we report that extensive base editing in exonic region can alter RNA splicing pattern, resulting in gene knockout. Altogether our work demonstrates that precision editing allows to design plant factors based on the knowledge on evolutionarily selected alleles and enlarge the gene pool to potentially provide advantageous phenotypes such as pathogen resistance.